FASTDash: A Visual Dashboard for Fostering Awareness in Software Teams - Biehl, Jacob; Czerwinski, Mary; Smith, Greg; Robertson, George; Bailey, Brian (CHI 2007 Conference on Human Factors in Computing Systems, 2007)
Software developers spend significant time gaining and maintaining awareness of fellow developers’ activities. FASTDash is a new interactive visualization that seeks to improve team activity awareness using a spatial representation of the shared code base that highlights team members’ current activities. With FASTDash, a developer can quickly determine which team members have source files checked out, which files are being viewed, and what methods and classes are currently being changed. The visualization can be annotated, allowing programmers to supplement activity information with additional status details. It provides immediate awareness of potential conflict situations, such as two programmers editing the same source file. FASTDash was developed through user-centered design, including surveys, team interviews, and in situ observation. Results from a field study show that FASTDash improved team awareness, reduced reliance on shared artifacts, and increased project-related communication. Additionally, the team that participated in our field study continues to use FASTDash.